Chinese Art and Its Encounter with the World : Negotiating Alterity in Art and Its Historical Interpretation - Clarke, David J. (David James), 1954- (Book collections on Project MUSE., 2011)
This book examines Chinese art from the mid-eighteenth century to the present, beginning with discussion of a Chinese portrait modeler from Canton who traveled to London in 1769, and ending with an analysis of art and visual culture in post-colonial Hong Kong. By means of a series of six closely-focused case studies, often deliberately introducing non-canonical or previously marginalized aspects of Chinese visual culture, it analyzes Chinese art's encounter with the broader world, and in particular with the West. Offering more than a simple charting of influences, it uncovers a pattern of richly mutual interchange between Chinese art and its others. Arguing that we cannot fully understand modern Chinese art without taking this expanded global context into account, it attempts to break down barriers between areas of art history which have hitherto largely been treated within separate and often nationally-conceived frames. Aware that issues of cultural difference need to be addressed by art historians as much as by artists, it represents a pioneering attempt to produce an art historical writing which is truly global in approach. It hopes to appeal both to those with a special interest in modern Chinese art and those who are only now becoming aware of this fascinating but previously under-explored field.